La protein regulates protein expression by binding with the mRNAs of target genes and participates the pathological process of ovarian cancer - Huang, Xuan; Zhu, Jialei; Li, Yueyan; Yu, Yang; Tang, Jing (Frontiers in Oncology, 2022)
Research on the mechanism and new targets of ovarian cancer is of great significance to reduce the high mortality and drug resistance of ovarian cancer. Human La protein has been found to be highly expressed in a variety of malignant tumors, and plays a role in tumorigenesis and development through its RNA binding function. However, its role and mechanism in ovarian cancer are not completely clear. The present study showed that La protein was highly expressed in serum and tissues of patients with ovarian cancer by ELISA and immunohistochemistry, and the high expression of La protein was associated with the increased degree of malignancy and poor prognosis by searching KM plotter database. Interference of La gene resulted in a significant decrease in the proliferation, migration and invasion of ovarian cancer cells with growth block in G1 phase and increasing apoptosis. By RNA binding protein immunoprecipitation, transcriptome sequencing and proteomics, 14 downstream target genes were screened. La protein might affect the protein expression of these 14 genes by binding with the mRNAs. Therefore, it played a role in the pathological process of ovarian cancer.